Effectiveness of Accelerating Policy of Tuberculosis Control to the National Tuberculosis Control Programme - กลัดพ่วง บุญเชิด; จิตต์วิวัฒน์ วรรณเพ็ญ; พูนพานิช ยุทธนา (Disease Control Journal, 2010)
This was an Intervention study aimed to demonstrate the effectiveness of policy advocacy to strengthen stopping tuberculosis. The results of study were compared with the performance of previous fiscal year. The study revealed that case detection increase to 13.07 %. Chest X-ray in prisoners showed abnormality compatible with Tuberculosis and sputum positive for Tuberculosis in prisoner were 5.4% and 0.49% respectively. Tuberculosis related with diabetes mellitus and others chronic disease were 8.16% and 6.48% respectively. The admission rate of sputum smear positive cases were 60.03%. This activity might pose a threat to health care worker in contraction tubercle bacilli, so it was extremely important to implement effective tuberculosis infection control strategy pararelly. The smear conversion rate was 89.00%. Regarding to HIV/TB activities, we found the antiHIV testing among tuberculosis patients and the access to ARV rate increased with statistic significant (P<0.001) 79.25% to 89.40% and 38.59% to 61.39% respectively. This study suggested that case finding active should be done in the high risk groups such as diabetic mellitus and others chronic disease. The strong political is obviously a strong driven mechanism to TB control at large.